Variables associated with the tolerance to water deficit in forage grasses - Machado, Regina C.R.; Souza, Hermínia M.F.; Moreno, Miguel A.; Alvim, Paulo de T. (Pesquisa Agropecuaria Brasileira, 2014)
The tolerance to water deficit of four tropical grasses was evaluated under field conditions. The leaf water potential, stomatal resistance, sprout height and leaf blade length were determined for Carimagua grass (Andropogon gayanus) buffel grass (Cenchrus ciliaris) cvs. Gayndah and Biloela, and Brachiaria Amazonian kikuyo grass (Brachiaria humidicola). The carimagua, ’Gayndah’ and Biloela’ grasses, under water deficit conditions, did not attain the critical level of leaf water potential for stomatal closing. The Amazonian kikuyo grass attained the lowest leaf water potential (-21 bars) and greatest diffusive stomatal resistance (20 seg. Cm-1) of the grasses studied here. The carimagua ’Gayndah’ and ’Biloela’ grasses also demonstrated, in relation to sprout height and leaf blade length, greater tolerance to water deficit than Amazonian kikuyo grass. Hence, the carimagua, ’Gayandah’ and Biloela’ grasses are a choice for areas where drought occurs for more than 120 days.